Pengaruh Good Corporate Governance Terhadap Profitabilitas pada Perusahaan Sektor Tambang yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Komang Ayu Malini Kriswari; Putu Sri Arta Jaya Kusuma (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of Good Corporate Governance (GCG) on the profitability of mining sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. The independent variables in this study include managerial ownership, institutional ownership, independent commissioners, and audit committee size, with firm size as a control variable. The data used is secondary data sourced from the companies' annual financial reports available on the official IDX website. Data analysis was conducted using panel data regression with the Random Effect Model (REM) approach. The results indicate that institutional ownership and audit committee size have a positive and significant effect on company profitability. Meanwhile, managerial ownership, independent commissioners, and firm size do not have a significant effect on profitability. These findings suggest that institutional shareholder involvement and an effective audit committee play a crucial role in improving company profitability. This research is expected to provide insights for mining companies to enhance the implementation of GCG principles and serve as a reference for investors and stakeholders in making sustainable strategic decisions.